Intelligent wheelchair simulator for users' training: Cerebral palsy children's case study - Faria, Brigida Monica (2019)
The use of real context simulation programs for training driving skills to control an intelligent wheelchair is an emergent area. The aim of this study is to verify if the exigency of use of the simulator of the IntellWheels project is adequate to the skills of children with cerebral palsy. A group study case was performed using children with cerebral palsy classified in the levels IV and V of the Gross Motor Function Classification System, aged between 6 and 12 years old. The user's performance in a wheelchair driving game using the Joystick and the Wiimote (for head movements' recognition) and the users' opinions about the system were studied. Results suggest that the system matches the children skills and it was verified that it was easier to drive the wheelchair with the joystick for most of the participants. Generally, the participants presented positive reactions, showing themselves satisfied with the experiment and convicted about the wheelchair future usability.